Analisis Strategi Promosi Bisnis UMKM Coffee Shop Dengan Menggunakan Media Sosial: Studi Kasus: Triple Seven Pangkalpinang - Lindiani Lindiani; Indah Registiana; Fauzan Fajrullah; Indah Noviyanti (Jurnal Bintang Manajemen, 2024)
This study aims to analyze the promotional strategies used by Micro, Small and Medium Enterprises (MSMEs) Coffee Shop, especially Triple Seven Pangkalpinang, through social media. The method used is descriptive analysis with a qualitative approach, where data is collected through direct observation, interviews with the owner, and documentation studies. The results showed that Triple Seven Pangkalpinang has implemented various promotional strategies through social media. In addition, it was found that the promotional strategy succeeded in increasing brand awareness and increasing customer interaction. In conclusion, the use of social media as a promotional tool for MSME Coffee Shops such as Triple Seven Pangkalpinang helps in the effectiveness to increase visibility and customer engagement, as well as strengthen their position in Pangkalpinang's local coffee industry.